Fighting Fire With Fires: The Fire‐Fuel Feedback Effect in Canadian Forests - Weiwei Wang; Xianli Wang; Tom Swystun; Tongli Wang; Jacqueline A. Oliver; Mike D. Flannigan; Wanli Wu; John L. Innes; Guangyu Wang (Global Ecology and Biogeography, 2026)
Aim Climate‐driven fire increases could be modified by fire‐fuel feedback, as recent fires reduce burnable fuels for future fires. Knowing the effects of fire‐fuel feedback is essential for more accurate projection of fire activity, which, however, has often been overlooked due to the challenge in its quantification. This study aims to project future fire activity under the changing climates with consideration for fire‐fuel feedback effects across Canada. Location Canadian forests. Time Period 1981–2100. Major Taxa Studied Trees. Methods We projected future changes in a full set of fire activity variables, including annual area burned (AAB), annual number of fires (ANF) and annual maximum fire size (MFS), based on extreme fire weather in Canada. We then incorporated fire‐fuel feedback into the projections to quantify its effects in Canadian forests and consequently answered the question of whether the unprecedented 2023 fire season would become a common occurrence in the future. Results The feedback from fires within 6–11 years prior showed the strongest power in rectifying fire activity projections, and the feedback effects strengthened as climate change became more severe. By century's end (2080s), under the extreme climate change scenario (RCP8.5), fire‐fuel feedback could reduce weather‐based AAB, ANF and MFS projections by 21%, 21% and 16%, respectively. Spatially, eastern and northwestern regions may see the greatest fire activity increases, while the strongest feedback effects appear in the south and northwest. In the 2080s, under RCP8.5, years with more extensive fires than 2023 may occur once every 9 years in regions most affected by the unprecedented 2023 fire season. Main Conclusions The results indicate that fire‐fuel feedback could modestly mitigate climate‐driven increases in future fire activity in Canadian forests. With more accurate projections that account for such feedback effects, the extraordinary 2023 fire season could be considered a low‐frequency but more plausible occurrence in the future.

Anticipatory governance for responsible investment in energy transition minerals in the Western Congo Basin - F.A Mboringong; R.A. Riggs; J.D. Langston; A.K. Boedhihartono; D. Endamana; Y. Ge; J.L Innes; J. Lu; P. Meyfroidt; L. Weng; J. Sayer (The Extractive Industries and Society, 2025)

Modeling the interactive effects of sea surface temperature, fishing effort, and spatial closures on reef fish populations - Anne A. Innes-Gold; Paul Carvalho; Lisa C. McManus; Seaenna Correa-Garcia; Stacia D. Marcoux; Kirsten L. L. Oleson; Kaci Stokes; Elizabeth M. P. Madin (Theoretical Ecology, 2024)

Variant-specific SARS-CoV-2 shedding rates in wastewater - Sarah M. Prasek; Ian L. Pepper; Gabriel K. Innes; Stephanie Slinski; Walter Q. Betancourt; Aidan R. Foster; Hayley D. Yaglom; W. Tanner Porter; David M. Engelthaler; Bradley W. Schmitz (Science of The Total Environment, 2023)

Comparing the effectiveness of twine- and binder-seeding in the Laminariales species Alaria esculenta and Saccharina latissima - Philip D. Kerrison; Mairi Innes; Adrian Macleod; Emily McCormick; Peter D. Elbourne; Michele S. Stanley; Adam D. Hughes; Maeve S. Kelly (Journal of Applied Phycology, 2020)
The continuing expansion of seaweed cultivation could assist in ensuring future global food security. The Laminariales species Alaria esculenta and Saccharina latissima are each cultivated for food across their European ranges. The predominant method for cultivating European kelps involves growing juveniles on twine within a hatchery which is then deployed at a farm site. The associated hatchery and deployment cost of this approach are relatively high. A new and innovative methodology—called binder-seeding—can reduce these costs, but, has yet to be validated. We compare the biomass yield and morphology of A. esculenta and S. latissima cultured using either the traditional twine-longline method or binder-seeding onto AlgaeRope and AlgaeRibbon, specially designed textiles. In a controlled growth experiment, A. esculenta had a similar biomass yield on all materials, but fronds were shorter (23 ± 7%) and thinner on the AlgaeRibbon (42 ± 4%) due to a 3–4-fold higher density of developing sporophytes compared to the twine-longline. In contrast, S. latissima gave a 4-fold higher biomass yield on the AlgaeRibbon in June (4.0 kg m −1 ), but frond morphology was not different between materials, despite a 4-fold higher sporophyte density on the AlgaeRibbon. The stipe length of both species also increased at the higher sporophyte density on the AlgaeRibbon. The AlgaeRope gave an intermediate response or was similar to the twine-longline. These results show that binder-seeding onto the AlgaeRibbon significantly increases the achieved biomass yield in S. latissima. These results can assist cultivators to select the most appropriate method of kelp cultivation depending on morphological/yield requirements of the end use. Further study is needed on the optimisation of the binder-seeding density and its impact on thallus morphology.

DArTseq molecular markers for resistance to Phytophthora cinnamomi in pineapple (Ananas comosus L.) - G. Sanewski; L. Ko; D. Innes; A. Kilian; J. Carling; J. Song (Australasian Plant Pathology, 2017)

Lateglacial and Holocene relative sea‐level changes and first evidence for the Storegga tsunami in Sutherland, Scotland - Antony J. Long; Natasha L. M. Barlow; Sue Dawson; Jon Hill; James B. Innes; Catherine Kelham; Fraser D. Milne; Alastair Dawson (Journal of Quaternary Science, 2016)
We reconstruct one of the longest relative sea‐level (RSL) records in north‐west Europe from the north coast of mainland Scotland, using data collected from three sites in Loch Eriboll (Sutherland) that we combine with other studies from the region. Following deglaciation, RSL fell from a Lateglacial highstand of +6−8 m OD (Ordnance Datum = ca. mean sea level) at ca. 15 k cal a BP to below present, then rose to an early Holocene highstand and remained at ca. +1 m OD between ca. 7 and 3 k cal a BP, before falling to present. We find no evidence for significant differential Holocene glacio‐isostatic adjustment between sites on the north‐west (Lochinver, Loch Laxford), north (Loch Eriboll) and north‐east (Wick) coast of mainland Scotland. This suggests that the region was rapidly deglaciated and there was little difference in ice loads across the region. From one site at the head of Loch Eriboll we report the most westerly sedimentary evidence for the early Holocene Storegga tsunami on the Scottish mainland. The presence of the Storegga tsunami in Loch Eriboll is predicted by a tsunami wave model, which suggests that the tsunami impacted the entire north coast of Scotland and probably also the Atlantic coastline of north‐west Scotland.

Unstable climate−growth relations for white spruce in southwest Yukon, Canada - Raphaël D. Chavardès; Lori D. Daniels; Patrick O. Waeber; John L. Innes; Craig R. Nitschke (Climatic Change, 2013)

Outcomes of reciprocal invasions between genetically diverse and genetically uniform populations of Daphnia obtusa (Kurz) - N. Tagg; D. J. Innes; C. P. Doncaster (Oecologia, 2005)

Forest community analysis and the point-centered quarter method - David M. Bryant; Mark J. Ducey; James C. Innes; Thomas D. Lee; Robert T. Eckert; Daniel J. Zarin (Plant Ecology, 2005)

The impacts of individual plant species on rhizosphere microbial communities in soils of different fertility - Louise Innes; Philip J. Hobbs; Richard D. Bardgett (Biology and Fertility of Soils, 2004)

Recognition of debris flow, debris flood and flood hazard through watershed morphometrics - D. J. Wilford; M. E. Sakals; J. L. Innes; R. C. Sidle; W. A. Bergerud (Landslides, 2004)

Genetic variation among life-history stages of mussels in a Mytilus edulis?M . trossulus hybrid zone - J. Toro; D. J. Innes; R. J. Thompson (Marine Biology, 2003)

Reproductive isolation and reproductive output in two sympatric mussel species (Mytilus edulis, M. trossulus) and their hybrids from Newfoundland - J. E. Toro; R. J. Thompson; D. J. Innes (Marine Biology, 2002)

Observation and Confirmation of Foliar Ozone Symptoms of Native Plant Species of Switzerland and Southern Spain - J. M. Skelly; J. L. Innes; J. E. Savage; K. R. Snyder; D. Vanderheyden; J. Zhang; M. J. Sanz (Water, Air, & Soil Pollution, 1999)

Morphological variation of Mytilus edulis and Mytilus trossulus in eastern Newfoundland - D. J. Innes; J. A. Bates (Marine Biology, 1999)

A molecular approach to the ecology of a mussel ( Mytilus edulis - M. trossulus ) hybrid zone on the east coast of Newfoundland, Canada - A. S. Comesaña; J. E. Toro; D. J. Innes; R. J. Thompson (Marine Biology, 1999)

Rpg1, a soybean gene effective against races of bacterial blight, maps to a cluster of previously identified disease resistance genes - T. Ashfield; J. R. Danzer; D. Held; K. Clayton; P. Keim; M. A. Saghai Maroof; D. M. Webb; R. W. Innes (Theoretical and Applied Genetics, 1998)

Allozyme and mitochondrial DNA variation in three species of oreos (Teleostei: Oreosomatidae) from Australasian waters - R. D. Ward; N.G. Elliott; P. M. Grewe; P. R. Last; P. S. Lowry; B. H. Innes; G. K. Yearsley (New Zealand Journal of Marine and Freshwater Research, 1998)
Collections of three species of oreos (smooth oreo, Pseudocyttus maculatus; black oreo, Allocyttus niger; and warty oreo, A. verrucosus ) from Australasian waters were examined for genetic variation. Allozyme heterozygosity was high in each species (25–29 loci: mean heterozygosity per locus per sample ranging from 0.100 to 0.148), but mitochondrial DNA variation was less extensive (10 six‐base restriction enzymes: nucleotide diversity ranging from 0.0012 to 0.0021). Collections of smooth oreos from Western Australia, Tasmania, and New Zealand did not permit the null hypothesis of a single stock to be confidently rejected. Black oreos from Tasmania and New Zealand were provisionally identified as separate stocks. Warty oreos from Tasmania were provisionally identified as separate from a Western Australia/New South Wales stock.

Does Lepidopteran Larval Crypsis Extend into the Ultraviolet? - Stuart C. Church; Andrew T. D. Bennett; Innes C. Cuthill; Sarah Hunt; Nathan S. Hart; Julian C. Partridge (The Science of Nature, 1998)

Genetic evidence for depth‐ and spatially separated stocks of the deep‐water spikey oreo in Australasian waters - N. G. Elliott; P. S. Lowry; P. M. Grewe; B. H. Innes; G. K. Yearsley; R. D. Ward (Journal of Fish Biology, 1998)
Samples of Neocyttus rhomboidalis from eight areas off southern Australia and eastern New Zealand were examined to assess the stock structure of the species. No spatial heterogeneity was detected for mitochondrial DNA variation after restriction analysis by two enzymes detecting polymorphic cut sites. Twenty mtDNA haplotypes were recorded, with an overall haplotype diversity of 0·683. Twenty‐eight allozyme loci were examined; the mean heterozygosity per locus was 13·0%. Significant sample heterogeneity was detected at three of twelve polymorphic loci: MPI*, PGM‐1 * and, most strikingly (G ST =0·43), sSOD *. Most of the sSOD * differentiation was associated with depth rather than geographical separation; sSOD * allele frequencies of shallow and deep samples being very different. It is suggested that the correlation between the sSOD * allele frequencies and depth is more likely to reflect natural selection than reproductive isolation. The spatial patterning of the MPI * and PGM‐1 * data suggest there are at least three geographic stocks of N. rhomboidalis in Australasian waters: (1) New Zealand, (2) Western Australia and South Australia, (3) west Tasmania to New South Wales and Lord Howe Rise.

Genetic population structure of southern bluefin tuna ( Thunnus maccoyii ) - P. M. Grewe; N. G. Elliott; B. H. Innes; R. D. Ward (Marine Biology, 1997)